Imbalance of world heritage list: Did the UNESCO strategy work? - Lasse Steiner; Bruno S. Frey (University of Zurich, Department of Economics, 2011)
The official intention of the UNESCO World Heritage List is to protect the global heritage. However, the imbalance of the distribution of Sites according to countries and continents is striking. Consequently, the World Heritage Committee launched the Global Strategy for a Balanced, Representative and Credible World Heritage List in 1994. To date, there have not been any empirical analyses conducted to study the impact of this strategy. This paper shows that the imbalance did not decrease and perhaps increased over time, thus reflecting the inability of the Global Strategy to achieve a more balanced distribution of Sites.
Keywords: Z11; D6; F5; H87; 330; UNESCO; international organizations; international political economy; global public goods; world heritage; Kulturgüter; Kulturpolitik; Internationale Organisation; Welt